2004
DOI: 10.1007/s00228-004-0745-0
|View full text |Cite
|
Sign up to set email alerts
|

The use of a cyclosporin?ketoconazole combination: making renal transplantation affordable in developing countries

Abstract: The use of KZ with CyA in renal transplant recipients with stable allograft function results in a significant reduction in the dose of CyA and a significant cost savings, without compromising patient or graft survival. The regimen may be useful in countries with limited resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…For expensive medications, this results in significant cost-savings to patients, insurance companies or governments that are responsible for paying for medications. This may be particularly valuable in making medications more accessible in developing countries with limited budgets for high-priced pharmaceuticals [5]. This strategy of adding an enzyme inhibitor to produce a clinically beneficial drug interaction is being successfully utilized in treating transplant patients and patients with HIV infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For expensive medications, this results in significant cost-savings to patients, insurance companies or governments that are responsible for paying for medications. This may be particularly valuable in making medications more accessible in developing countries with limited budgets for high-priced pharmaceuticals [5]. This strategy of adding an enzyme inhibitor to produce a clinically beneficial drug interaction is being successfully utilized in treating transplant patients and patients with HIV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Florea et al [8] reported a 48% decrease in the total daily dose of cyclosporine when administered with itraconazole while another study found that cyclosporine dose could be reduced by 23%, 40%, 75% and 80% when combined with diltiazem, itraconazole, ketoconazole or ketoconazole plus diltiazem, respectively [9]. Gerntholtz et al [5] reported an 85% reduction in cyclosporine dose with ketoconazole and suggested that this combination was critical in making transplantation more affordable in developing countries. A similar assertion was made by Egyptian investigators who used the combination for the treatment of nephrotic syndrome in children [10].…”
Section: Boosted Regimens For Treating Hiv Infectionmentioning
confidence: 99%
“…The dose used in different studies as varied from 54 to 200 mg/day [8,10,[18][19][20][21]. In general, studies that have used higher dosage have shown greater inhibition, suggesting the possibility of a dose response.…”
Section: Time After Starting Ketoconazolementioning
confidence: 99%
“…Inhibitors of the CYP3A enzyme system such as diltiazem, ketoconazole, and fluconazole retard CNI metabolism leading to the reduction in the dose required to maintain adequate drug level [6,7] and are used in developing countries for reducing cost [8][9][10][11]. The degree of metabolic inhibition depends upon the abundance of the enzyme.…”
Section: Introductionmentioning
confidence: 99%
“…[789] Some transplant centers reported the intentional use of drugs that interfere with the P450 enzyme system, such as diltiazem, erythromycin or the azole ketoconazole, to reduce the CyA dose while maintaining therapeutic blood cyclosporine concentrations. [6810111213] Azoles inhibit fungal growth by competing with and blocking the cytochrome P450, family 3, subfamily A (cytochrome P3A4)-dependent enzyme lanosterol 14-α-demethyase, which catalyzes the synthesis of the major sterol component of fungal plasma membrane, ergosterol. The nonselective azole, ketoconazole, cross-inhibits mammalian CYP3A4 resulting in up to 80% reduction of the metabolism of CyA.…”
Section: Introductionmentioning
confidence: 99%